2015
DOI: 10.1039/c5cp00602c
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state185/187Re NMR and GIPAW DFT study of perrhenates and Re2(CO)10: chemical shift anisotropy, NMR crystallography, and a metal–metal bond

Abstract: Advances in solid-state nuclear magnetic resonance (SSNMR) methods, such as dynamic nuclear polarization (DNP), intricate pulse sequences, and increased applied magnetic fields, allow for the study of systems which even very recently would be impractical. However, SSNMR methods using certain quadrupolar probe nuclei (i.e., I > 1/2), such as (185/187)Re remain far from fully developed due to the exceedingly strong interaction between the quadrupole moment of these nuclei and local electric field gradients (EFGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 167 publications
0
28
0
Order By: Relevance
“…This demonstrates the particular sensitivity of NMR interactions to the precise positions of atoms in the crystal. Other recent NMR crystallography examples highlight the combined utility of the quadrupolar interaction, chemical shift tensor, and dipolar coupling constant for providing structural insights in metal complexes and sodium diphosphates Widdifield et al, 2015).…”
Section: Applications and Examplesmentioning
confidence: 99%
“…This demonstrates the particular sensitivity of NMR interactions to the precise positions of atoms in the crystal. Other recent NMR crystallography examples highlight the combined utility of the quadrupolar interaction, chemical shift tensor, and dipolar coupling constant for providing structural insights in metal complexes and sodium diphosphates Widdifield et al, 2015).…”
Section: Applications and Examplesmentioning
confidence: 99%
“…For instance, for a spin 5/2 nucleus, the observed transitions are typically ±1/2 → ±3/2 and ±3/2 →±5/2. It is to be noted that the overtone transition, ±1/2 → ±5/2, can sometimes be observed . As the Boltzmann spin population is proportional to the difference in the energy levels, the sensitivity of NQR experiments generally increases with the magnitude of the QI.…”
Section: Review Of Basic Theorymentioning
confidence: 99%
“…It is observed that the observed EFG tensor is quite sensitive to whether the chlorine ligand is bridging, terminal-axial or terminalequatorial. An experimental and theoretical NMR study of 185/187 Re has been carried out on several perrhenates (KReO4, AgReO4, Ca(ReO4)22H2O), ReO3, and Re2(CO)10 ( Widdifield et al, 2015). The 77 Se chemical shift tensor for L-selenocystine has also been measured in the solid state (Struppe et al, 2015).…”
Section: Physical Aspects Of Nuclear Shieldingmentioning
confidence: 99%